Kingdom of the Netherlands-Netherlands Antilles : Staff Report for the 2001 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2001)
The past decade has witnessed a progressive weakening of the Antillean economy, and prospects for a recovery depend on reinvigorating and sustaining adjustment. There is a need for more vigorous reforms, well coordinated across governments and supported by building social consensus. Fiscal policy can support growth over the medium term by reforming the tax system and lowering the tax and administrative burden on the private sector. Continuing progress with structural reforms is critical to improve the prospects for job creation and economic growth.